Pengaruh Kualitas Pelayanan terhadap Kepuasan Pasien Ruang Rawat Inap Kebidanan: The Effect of Service Quality on Obstetric Inpatients - Mariah, Vina; Ciptiasrini, Uci; Ernita (Dohara POAJ, 2021)
Introduction: Service quality refers to the level of perfection of health services in meeting the needs of each customer. So, the quality of health is to meet the needs and satisfying services, which if the service is satisfactory it will lead to a sense of satisfaction with the health that is held. The purpose of the study was to determine the effect of service quality on patient satisfaction in obstetrics at RSDH Cianjur. Methods: This research is a quantitative type with an analytic nature with a cross-sectional study. The population in this study were obstetric inpatients at RSDH Cianjur. The sample in this study was 98 respondents. Researchers used the Chi-Square test. Results: Based on the research, it is known that most of the patients stated that they were satisfied as many as 60 people (61.2%) and most of the patients stated that the service quality was good as many as 51 people (52%). Statistical test results There is a relationship between service quality and patient satisfaction in obstetrics at RSDH Cianjur r with P-value = 0.009 and OR = 3.322. In conclusion, there is an effect of service quality on the satisfaction of obstetric inpatients at RSDH Cianjur. Discussion: There is an effect of service quality on the satisfaction of obstetric inpatients at RSDH Cianjur.